Two-dimensional graphene-like C2N: an experimentally available porous membrane for hydrogen purification. Issue 23 (21st June 2015) - Xu, B.; Xiang, H.; Wei, Q.; Liu, J. Q.; Xia, Y. D.; Yin, J.; Liu, Z. G.
<x xml:space="preserve">Abstract</x> The two-dimensional porous C2N sheet exhibits an extremely high selectivity and large permeance in favour of H2 among other atmospheric gases.